Mapping where patients access primary care providers. - Frymire, Eliot; Gozdyra, Peter; Green, Michael; Bayoumi, Imaan; Glazier, Richard; Jaakkimainen, Liisa; Khan, Shahriar; Kiran, Tara; Premji, Kamila (International Journal of Population Data Science, 2022)
Objectives To gain an understanding of the attribution of patients to newly introduced Ontario Health Teams (OHT). OHTs are responsible for organizing and delivering health local care based on established connections between patients, their primary care providers, and hospitals. Furthermore, we aim to identify areas with poor geographic access to care. Approach We used GIS analyses and maps to depict the attribution of patients to OHTs based on their uptake of primary care and hospital referral patterns. Residents of a specific local area can be attributed to different OHTs based on their prevailing health seeking choices. This leads to a creation of non-unique OHT ‘capture zones’, which may pose challenges in primary health care planning and delivery. The range of spatial analyses and maps used in this study helps to overcome some of these limitations and provides healthcare administrators with important geographic layer of information not available through other data summary methods. Results The distribution of patients and patterns of the primary care seeking vary greatly between urban, rural and remote areas. Many of the rural and remote OHTs have their patients clustered in areas surrounding the main hospital. These areas can be quite large geographically but their extents are still unique from other OHTs. OHTs in urban areas show substantial overlaps of their patient base. The urban patients are in most cases highly clustered around the main hospital location for hospitals providing primary and secondary care. The distribution of patients attributed to OHTs with hospitals providing tertiary care is quite spread out throughout the region or even the province. All these unique patterns reflect complex ways of primary care seeking behavior and referral patterns for hospital care. Conclusion These attribution maps and data tables are an essential resource for planners and decisions makers in identifying priorities within the regional provision of primary care. This knowledge is essential to a better understanding of health care needs of local populations, and to implementing improvements in health care access.